On the calculation of certain singular integrals - Kovalenko, I. L.; Litvin, A. I.; Simonzhenkov, S. D. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
A method for the approximate calculation of Cauchy-type integrals with logarithmic singularities is proposed. It is based on the expansion of a function $f(x)$ in a series in the Chebyshev polynomials.